2013
DOI: 10.1021/ja407526s
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 and H4 N-Terminal Tails in Nucleosome Arrays at Cellular Concentrations Probed by Magic Angle Spinning NMR Spectroscopy

Abstract: Chromatin is a supramolecular assembly of DNA and histone proteins, organized into nucleosome repeat units. The dynamics of chromatin organization regulates DNA accessibility to eukaryotic transcription and DNA repair complexes. However, the structural and dynamic properties of chromatin at high concentrations characteristic of the cellular environment (> ~200 mg/ml) are largely unexplored at the molecular level. Here, we apply magic angle spinning nuclear magnetic resonance to directly probe the dynamic histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 36 publications
10
83
0
Order By: Relevance
“…For instance, the amplitude of fluctuations of the H3 tail on one side of nucleosome, which adsorbed on the linker DNA, was much higher (due to linker DNA flexibility) compared to the other H3 tail, which was compactly folded at the DNA entry/exit sites. The dynamical scales of histone tails in mononucleosomes and nucleosomal arrays were recently probed by a number of techniques including solution, solid state NMR and hydrogen exchange studies [3133]. They reported rather controversial findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the amplitude of fluctuations of the H3 tail on one side of nucleosome, which adsorbed on the linker DNA, was much higher (due to linker DNA flexibility) compared to the other H3 tail, which was compactly folded at the DNA entry/exit sites. The dynamical scales of histone tails in mononucleosomes and nucleosomal arrays were recently probed by a number of techniques including solution, solid state NMR and hydrogen exchange studies [3133]. They reported rather controversial findings.…”
Section: Resultsmentioning
confidence: 99%
“…The microsecond timescale as well as nucleosome models with the realistic DNA linker segments and multiple comparative simulations enabled us to get insights into the functionally relevant rearrangements in nucleosome including the coupling between the conformations of histone tails and the DNA geometry. While many functionally relevant motions may occur on much longer time scales [10], several NMR studies recently suggested that histone tails showed sub-microsecond dynamics providing possibility to compare our computational results with the experimental data [3133]. …”
Section: Introductionmentioning
confidence: 99%
“…Sedimentation has been widely used to study the folding and compaction of nucleosomes and nucleosomal arrays 5. Jaroniec and co‐workers were the first to realize the great potential of ssNMR spectroscopy in the context of nucleosomes through their study on histone tails in nucleosomal arrays 6. Herein, we introduce the use of nucleosome sedimentation, ultra‐fast magic angle spinning (MAS), and 1 H‐detected ssNMR spectroscopy to characterize the structure and dynamics of nucleosomes and their protein complexes.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In spite of the latest advances, [6,7] high-throughput protein structure elucidation by conventional ssNMR methods remains challenging due to difficulties in obtaining critical non-local contacts.D uring the past decade,s sNMR measurements of nuclear paramagnetic relaxation enhancements (PREs) have been explored for structural studies of native metalloproteins [8,9] and proteins modified with covalent paramagnetic tags,including nitroxide spin labels [10] and metal chelates. [1][2][3][4][5] In spite of the latest advances, [6,7] high-throughput protein structure elucidation by conventional ssNMR methods remains challenging due to difficulties in obtaining critical non-local contacts.D uring the past decade,s sNMR measurements of nuclear paramagnetic relaxation enhancements (PREs) have been explored for structural studies of native metalloproteins [8,9] and proteins modified with covalent paramagnetic tags,including nitroxide spin labels [10] and metal chelates.…”
mentioning
confidence: 99%
“…Magic-angle spinning solid-state nuclear magnetic resonance (ssNMR) has emerged as av iable tool for analysis of the structure and dynamics of biomacromolecular complexes and assemblies including membrane proteins,a myloids,v iral capsids,a nd chromatin. [1][2][3][4][5] In spite of the latest advances, [6,7] high-throughput protein structure elucidation by conventional ssNMR methods remains challenging due to difficulties in obtaining critical non-local contacts.D uring the past decade,s sNMR measurements of nuclear paramagnetic relaxation enhancements (PREs) have been explored for structural studies of native metalloproteins [8,9] and proteins modified with covalent paramagnetic tags,including nitroxide spin labels [10] and metal chelates. [11][12][13] These paramagnetic methods are capable of providing information about electronnucleus distances up to~20 ,p roviding valuable information for structure determination.…”
mentioning
confidence: 99%